WANITA DALAM POLIGAMI (STUDI PEMIKIRAN MUHAMMAD SYAHR) - Abdul Jalil (CENDEKIA: Jurnal Studi Keislaman, 2016)
What does Islam say about polygamy is still being debated that were kept warm for discussion. This debate has spawned various product ideas with arguments and interpretations. Muhammad Shahrur, a controversial figure, tried to give an understanding and interpretation different with the contemporary scholars on the issue of polygamy. According to Muhammad Shahrur, women who may be appropriate for polygamy, corresponding to content of Surah an-Nisa ': 2-3, is the only widow with orphans. Therefore the spirit and purpose of limusa’adatil aramil wal aitam, helping widows and orphans, are highly relevant to maqasid asy-syari’ah.